Cloning, characterization and expression of a 200 Kilodalton diagnostic antigen of Babesia bigemina - Tebele, N.; Skilton, Robert A.; Katende, J.; Wells, C.W.; Nene, Vishvanath M.; McElwain, T.F.; Morzaria, S.P.; Musoke, A.J. (American Society for Microbiology, 2000)
Current serological tests for Babesia bigemina use semipurified merozoite antigens derived from infected erythrocytes. One of the major drawbacks of these tests is that antigen quality can vary from batch to batch. Since the quality of the antigen contributes to the sensitivity and specificity of serological tests, the use of standardized recombinant antigens should ensure consistency in assay quality. Previously, a 200-kDa merozoite antigen (p200) was identified as a candidate diagnostic antigen for use in a serological assay for the detection of B. bigemina antibodies in infected cattle. In this study, we have cloned, characterized, and expressed p200. A 3.5-kbp cDNA clone encoding p200 was isolated and shown to be almost full length, lacking approximately 300 bp at the 5' end. The predicted amino acid sequence shows that p200 consists of a long, highly charged central repeat region of an uninterrupted alpha helix, indicative of a fibrous protein. Immunoelectron microscopy localized p200 to the merozoite cytoplasm, suggesting that the antigen may be a structural protein involved in forming filament structures within the cytoskeleton. The 3.5-kbp cDNA was expressed in bacteria as a fusion protein with glutathione S-transferase (GST), but the yield was poor. To improve the yield, cDNA fragments encoding antigenic domains of p200 were expressed as fusions with GST. One of these fusion proteins, C1A-GST, is composed of a 7-kDa fragment of the p200 repeat region and contains epitopes that react strongly with sera from cattle experimentally infected with B. bigemina. Recombinant C1A-GST should permit the development of an improved enzyme-linked immunosorbent assay for the detection of antibodies against B. bigemina.